2017
DOI: 10.1007/s00421-017-3698-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aerobic fitness on vasoreactivity in young men

Abstract: This work supports an association between L-FMC and aerobic fitness in young, healthy men. Longitudinal or interventional studies are warranted to support causality, and to distinguish whether L-FMC is more sensitive to changes in aerobic fitness than FMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Although a tendency for a decrease was noted (p = 0.083), sitting did not significantly impact Tone%, a measure believed to reflect the vasoactive balance between dilator and constrictor pathways. 3 We would like to note, after sitting HRV responses did favor greater parasympathetic activity (i.e., greater SDNN, and lower LF), which should correspond to a decrease in Tone%.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Although a tendency for a decrease was noted (p = 0.083), sitting did not significantly impact Tone%, a measure believed to reflect the vasoactive balance between dilator and constrictor pathways. 3 We would like to note, after sitting HRV responses did favor greater parasympathetic activity (i.e., greater SDNN, and lower LF), which should correspond to a decrease in Tone%.…”
Section: Discussionmentioning
confidence: 87%
“…Data were consolidated into 1-second bins and processed through a custom calculation macro (visual basic; Microsoft Excel). 3 Diameter and blood velocity data from the 2-minute baseline recording were averaged (Diamrest), and the largest diameter after cuff release during the FMD was considered peak (Diampeak), and used to calculate FMD in both absolute (mm) and relative (%) terms; i.e., FMD change = (Diampeak − Diamrest)/Diamrest × 100. Shear rate (s −1 ) was calculated as 4 × mean blood velocity/diameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has indicated that the YMCA cycle test provides a valid and reliable estimate of VO 2 max in healthy individuals ( Beekley et al, 2004 ; McArdle et al, 2010 ). This test was commonly used in studies similar to age group in the present study ( Siconolfi et al, 1982 ; Marks et al, 1999 ; Zhang and Ye, 2005 ; Bell et al, 2017 ; Shi et al, 2018 ). In this protocol, the participants performed consecutive stages, each with increasing force, and lasting for 3 min.…”
Section: Methodsmentioning
confidence: 92%
“…In contrast to the radial artery, there is no homogeneous vasoreactivity to the low‐flow condition in the brachial artery, with reports of vasodilation, vasoconstriction and no alteration . Bell, et al reported good between‐day reliability of the L‐FMC measurement in the brachial artery of adults (ICC of 0.87). Additionally, Aizawa, et al reported a significant association between L‐FMC and FMD in adults, suggesting that low‐flow vasoreactivity contributes to the magnitude of the FMD response.…”
Section: Introductionmentioning
confidence: 99%